Promoting Agricultural Growth, Technology Adoption, and Crop Diversity in Bangladesh - Akhter Ahmed - Ahmed, Akhter; Ahmed, Akhter (2017)
A presentation by Dr. Akhter Ahmed, IFPRI Country Representative for Bangladesh, at IFPRI's workshop, "Eliminating Hunger and Malnutrition: Are Sustainable Solutions in Sight?" on October 4, 2017 in Dhaka, Bangladesh.